2019
DOI: 10.1016/j.apsusc.2018.10.269
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive PNIPAM grafted alginate/chitosan PEC

Abstract: Smart biomaterial functionality such as controlled adhesion properties is crucial to limit strip-<>ff injuries. Among functional polymers, poly•N(isopropylacrylamide) (PNIPAM) allows surface properties to be changed depending on the temperature, with a transition of its properties that occurs around 32 •c, called the lower critical solution temperature (LCST). This transition is expected to modify surface interactions. Alginate and chitosan are bio compatible polymers commonly combined as polyelectrolyte compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Chitosan has a highly regular structure consisting of β -(1→4) linked D-glucosamine repeating units with three reactive groups, giving many possibilities of functionalization. Among the various methods, graft modification is considered as a convenient and promising approach to expand the applicability and functionality of chitosan [2,3,4,5,6,7,8]. However, the conventional grafting techniques on chitosan do not give control on the side polymer chain lengths and composition, the number of grafting sites, and grafting percentage.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan has a highly regular structure consisting of β -(1→4) linked D-glucosamine repeating units with three reactive groups, giving many possibilities of functionalization. Among the various methods, graft modification is considered as a convenient and promising approach to expand the applicability and functionality of chitosan [2,3,4,5,6,7,8]. However, the conventional grafting techniques on chitosan do not give control on the side polymer chain lengths and composition, the number of grafting sites, and grafting percentage.…”
Section: Introductionmentioning
confidence: 99%
“…The first layer of the alginate hydrogel network structure coated the whole nanofibrous sheet, and in the second layer, alginate penetrated into the sheet and covered the PCL/chitosan nanofibers individually. The great swelling ability of fibers facilitated the infiltration of alginate into each PCL/chitosan nanofiber and caused electrostatic interaction between amine groups of chitosan and carboxyl groups of alginate 48 . This novel scaffold has created a more interconnected nanoporous layer that is vital to let nutrients diffuse to cells within the construct and take waste products out of the scaffold 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The chemical modification strategy was based on previously reported studies 18 . Briefly, the hydroxyl groups of PCL and PLA cannot react easily with the carboxylate groups of alginate and consequently these have to be activated by EDC.…”
Section: Methodsmentioning
confidence: 99%
“…However, the properties of these potential biomaterials are also strongly dependent on their surface characteristics, given the fact that body/biomaterial interface is crucial for cell or protein interactions with the implant. We believe that alginate and chitosan PEC can be a useful platform, and have previously tailored its surface and thus functional properties by modifying its surface chemistry through the action of PNIPAM, a thermosensitive polymer, 17 and showed that interactions with inert surfaces, 18 cells and tissues 19 can be controlled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation